Design of triple‐band dual‐sense shared aperture circular polarized antenna for multimode BeiDou communication and navigation integration. Issue 8 (16th May 2022) - Liu, Hongmei; Wang, Yao; Yu, Da; Fang, Shaojun; Wang, Zhongbao
Abstract: In the article, a triple‐band dual‐sense shared aperture circular polarized (CP) antenna is proposed for multimode BeiDou communication and navigation applications. By integrating the stub‐loaded rectangle patch with the shorting‐pin‐loaded ring patch, the coverage of GPS L2, GPS L5, BDS‐2 B2, BDS‐2 B3, and BDS‐1 L/S bands is realized. Besides, wideband filtering orthogonal feed network is adopted for feeding the ring patch to reduce the mutual coupling interference between the two patches. The slot‐loaded ground plane is also employed for further decoupling. For validation, a prototype is designed, fabricated, and measured. The results indicate that the polarization of right‐handed circular polarization (RHCP) is obtained at 1.2 GHz with a peak gain of 5.4 dBic for navigation service. While left‐handed circular polarization (LHCP) and RHCP are realized at 1.615 GHz and 2.49 GHz, respectively, with the peak gains of 6.7 dBic and 7.4 dBic for communication service.